Key management in tree shaped hierarchies - Lopriore, Lanfranco (Information security journal., 2018)
We refer to an access control system based on subjects and objects. Subjects are active entities, e.g. processes, while objects are passive entities, e.g. messages exchanged between the nodes of a distributed computing environment. The system is partitioned into security classes organized into a tree shaped hierarchy. A subject assigned to a given class can access the objects in this class and in all the classes that descend from this class in the class hierarchy. To this aim, a key is associated with each class. A mechanism of the protection system, called key derivation, allows a subject that holds the key of a given class to transform this key into the keys of the descendant classes. This mechanism is based on a single, publicly known one-way function. If the class hierarchy is modified, by adding a new class or deleting an existing class, the necessary form of key redistribution is partial, and is limited to the classes in the subtree of the root that is involved in the change.